2013
DOI: 10.1074/jbc.m113.492397
|View full text |Cite
|
Sign up to set email alerts
|

A Lactobacillus rhamnosus GG-derived Soluble Protein, p40, Stimulates Ligand Release from Intestinal Epithelial Cells to Transactivate Epidermal Growth Factor Receptor

Abstract: Background: p40 is a Lactobacillus rhamnosus GG-derived protein.Results: p40 stimulates ADAM17 activation and HB-EGF release, which is required for EGF receptor transactivation, prevention of apoptosis, and preservation of barrier function in intestinal epithelial cells. Conclusion: p40 transactivates the EGF receptor through ADAM17-mediated HB-EGF release in intestinal epithelial cells. Significance: These results define a mechanism of p40 in modulating intestinal epithelial cell homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 49 publications
3
115
1
3
Order By: Relevance
“…We have reported that EGFR transactivation by p40 occurs through the release of an EGFR ligand, HB-EGF. Thus, p40 stimulates a delayed (30 min) and longer period of EGFR activation (up to 2 h), compared with HB-EGF (15-30 min) (24). This study further showed that p40 stimulated several peaks of EGFR activation, which are correlated with increased Muc2 gene expression at these time points in LS174T cells.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…We have reported that EGFR transactivation by p40 occurs through the release of an EGFR ligand, HB-EGF. Thus, p40 stimulates a delayed (30 min) and longer period of EGFR activation (up to 2 h), compared with HB-EGF (15-30 min) (24). This study further showed that p40 stimulated several peaks of EGFR activation, which are correlated with increased Muc2 gene expression at these time points in LS174T cells.…”
Section: Discussionsupporting
confidence: 58%
“…To elucidate the mechanisms of probiotic action, we purified and cloned p40 from LGG culture supernatants. p40 has beneficial effects on colon epithelial homeostasis through activation of EGFR and Akt in intestinal epithelial cells (23)(24)(25). In the present study, we demonstrate that p40 promotes Muc2 gene expression and MUC2 production in LS174T cells, which requires EGFR activation.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Briefly, 96-well microtiter plates were (passage 7-15) were used according to the protocol described by Whitehead et al (17). Briefly, the cells were maintained in RPMI 1640 medium (Thermo Fisher Scientific) containing 5% heatinactivated fetal bovine serum (Thermo Fisher Scientific), 5 U/mL mouse interferon-γ (IFN-γ; PeproTech, Rocky Hill, NJ, USA), 100 unit/mL penicillin, 100 μg/mL streptomycin (Thermo Fisher Scientific), 5 μg/mL insulin, 5 μg/mL transferrin and 5 ng/mL selenous acid (#354351; BD Biosciences, San Jose, CA, USA) at 33°C as permissive conditions in a water-saturated atmosphere incubator with 5% CO 2 (18). Before experiments, the medium was replaced with one without IFN-γ and the cells were moved to 37°C (a nonpermissive temperature) for 24 h to allow them to differentiate.…”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%